APPLICATION OF JIGSAW LEARNING METHOD TO IMPROVE ISLAMIC RELIGIOUS EDUCATION LEARNING ACHIEVEMENT IN GRADE V OF STATE ELEMENTARY SCHOOL 040447 KABANJAHE - Siti Astari Litami Damanik (CV. Asry Persada Quality, 2025)
This study aims to determine the application of the jigsaw learning method can improve the learning achievement of Islamic Religious Education subjects of grade V students of SD Negeri 040447 Kabanjahe. This research was conducted at SD Negeri 040447 Kabanjahe. The subjects of this study were grade V students of SD Negeri 040447 Kabanjahe. The number of grade V students of SD Negeri 040447 Kabanjahe is 33 students consisting of 15 male students and 18 female students. The techniques used to collect data in this study were tests, observations and documentation. This research was conducted by applying the jigsaw learning method which has been carried out for three cycles, it can be concluded that learning by applying the jigsaw learning method has a positive impact on improving student learning achievement with an average value of 78.12 in cycle I, becoming 81.79 in cycle II and increasing again to 86.88 in cycle III. The success of the learning process is marked by an increase in student learning completion in each cycle, namely cycle I (51.52%), cycle II (60.61%) cycle III (84.85%). The conclusion is that the application of the jigsaw learning method improves the learning achievement of Islamic Religious Education subjects for grade V students of SD Negeri 040447 Kabanjahe.